Energy drinks may affect the ovarian reserve and serum anti-mullerian hormone levels in a rat model - (:unkn) unknown (GALENOS YAYINCILIK, 2021)
Objective: Energy drinks have an impact on concentration levels, physical performance, speed of reaction, and focus, but these drinks cause many adverse effects and intoxication symptoms. The main goal of this study was to determine the effect of energy drink consumption on ovarian reserve and serum anti-mullerian hormone (AMH) levels. Materials and Methods: Female Wistar albino rats (n=16) were included and randomized into two groups (n=8). Serum AMH levels were checked before and after energy drinks were given. Eight weeks later, the ovaries and uteruses of the rats were analyzed histopathologically. The number of follicles in the ovaries was counted. Results: The total number of the preantral plus small antral follicles, which show the ovarian reserve, was decreased at the end of eight weeks in both the control group and the energy drink group. There was a statistical difference between them (p=0.021). Also, there was a statistically significant difference in the initial/final AMH (ng/mL) reduction levels between the control group and the energy drink group (p=0.002). AMH levels were decreased more in the energy drink group. Conclusion: The consumption of energy drinks can lead to a decrease in ovarian reserve and AMH values and may cause weight gain.
Keywords: Energy drinks; anti-mullerian hormone; ovarian reserve; antral follicles; FOLLICLE DEVELOPMENT; TAURINE; CAFFEINE; CONSUMPTION; DETORSION; BEVERAGES